2012
DOI: 10.1097/mlr.0b013e318241e8e1
|View full text |Cite
|
Sign up to set email alerts
|

What Did the Doctor Say? Health Literacy and Recall of Medical Instructions

Abstract: Background Limited literacy has repeatedly been linked to problems comprehending health information, although the majority of studies to date have focused on reading various print health materials. We sought to investigate patients’ ability to recall spoken medical instructions in the context of a hypothetical clinical encounter, and whether limited health literacy would adversely affect performance on the task. Methods A total of 755 patients age 55–74 were recruited from one academic internal medicine clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 37 publications
6
112
0
5
Order By: Relevance
“…However, both English-and Spanish-speaking patients likely rely heavily on verbal communication and instructions given during the office visit, and this may particularly be true for patients with low health literacy. 17 For example, patients with low health literacy often compensate with greater reliance on the physician for health information. 18 As expected, health literacy levels were lower among Spanish-speaking patients in our study, but we did not find any significant difference in the recall of medications.…”
Section: Discussionmentioning
confidence: 99%
“…However, both English-and Spanish-speaking patients likely rely heavily on verbal communication and instructions given during the office visit, and this may particularly be true for patients with low health literacy. 17 For example, patients with low health literacy often compensate with greater reliance on the physician for health information. 18 As expected, health literacy levels were lower among Spanish-speaking patients in our study, but we did not find any significant difference in the recall of medications.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 From this point of view, limited health literacy produces a vicious cycle, which engenders professional dominance and patient disengagement. 26 Actually, patients living with limited health literacy are likely to: exhibit impaired ability to recall health information, 27 perceive low self-efficacy in understanding and using prescription medication, 28 be unable to devise appropriate strategies to improve medication usage, 29 reveal health exacerbation, 30 show repeated and serious medication errors, and cause high medical expenses. 31 Several studies have discussed health literacy as a significant barrier to medication adherence, 32,33 although other scholars support that the relationship between these two dimensions is not clear.…”
Section: Simondsmentioning
confidence: 99%
“…A previous study [24] investigated patients' health literacy skills and recall of spoken medical instructions. It showed that the majority of patients had adequate health literacy, and that they could correctly recall spoken information.…”
Section: Discussionmentioning
confidence: 99%